A visit to Instituto Cervantes - Azlina, Mohd Ariffin (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
21 September 2012. The Espansia Club organized a one-day educational trip to Instituto Cervantes in Damansara Heights, Kuala Lumpur on 21 September 2012. Instituto Cervantes de Kuala Lumpur is a resource center, which serves anyone interested to learn about Spain, its language, culture and other Spanish-speaking countries.